2021
DOI: 10.2196/31293
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Videoconference-Delivered Cognitive Behavioral Therapy for Adults With Psychiatric Disorders: Systematic and Meta-Analytic Review

Abstract: Background Cognitive behavioral therapy (CBT) is the gold standard of psychotherapy for psychiatric disorders. However, the format of delivering CBT in person limits access to the intervention. The advancements in information and communication technology, especially the internet, present an opportunity for cognitive behavioral therapists to service patients or clients in remote areas through videoconferencing. Although many randomized controlled trials of videoconference-delivered cognitive behavio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 71 publications
2
22
0
1
Order By: Relevance
“…Cognitive-behavioral therapy is a highly effective psychotherapy for major depressive disorder, anxiety disorders, and PTSD [ 55 , 56 ]. Internet-Based CBT (ICBT) via videoconference or web-based program also is as effective as face-to-face CBT [ 57 59 ]. Remote treatment such as ICBT does not require people to visit the hospital and may help reduce the risk of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive-behavioral therapy is a highly effective psychotherapy for major depressive disorder, anxiety disorders, and PTSD [ 55 , 56 ]. Internet-Based CBT (ICBT) via videoconference or web-based program also is as effective as face-to-face CBT [ 57 59 ]. Remote treatment such as ICBT does not require people to visit the hospital and may help reduce the risk of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…For example, systematic reviews of randomized, quasi‐experimental, and uncontrolled clinical trials indicate that VCP may be associated with medium to large effects on depressive symptoms (Berryhill, Culmer, et al., 2019 ) and small to large effects on symptoms of anxiety (Berryhill, Halli‐Tierney, et al., 2019 ). Similarly, a meta‐analysis of 16 studies evaluating the effectiveness of cognitive behavioral VCP further demonstrated that, relative to various control conditions, VCP appears to produce moderate effects across multiple outcome measures and presenting concerns (Matsumoto et al., 2021 ). Finally, data from a recent multilevel meta‐analysis additionally reported no significant differences in outcomes between clients receiving either IP or VCP services (Batastini et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated the efficacy of CBT in psychiatric disorders ( Butler et al, 2006 ; Hofmann et al, 2012 ; Van Dis et al, 2020 ; Matsumoto et al, 2021 ). 269 quantitative meta-analyses were identified in a review to verify the effectiveness of CBT for psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…And CBT demonstrated superior efficacy as compared to other forms of psychotherapies in personality disorders, bulimia, positive symptoms in schizophrenia ( Hofmann et al, 2012 ). A study showed that a pooled effect size (Hedge g) post-treatment of −0.49 (95% CI −0.68 to −0.29), which indicated CBT had a significant effect on psychiatric disorders ( Matsumoto et al, 2021 ). Moreover, much evidence addressed that CBT produced long-term persistence of therapeutic effects following the termination of treatment ( Butler et al, 2006 ; Van Dis et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%